Malathion biodegradation by a psychrotolerant bacteria Ochrobactrum sp. M1D and metabolic pathway analysis. (15th June 2021) - Verma, S.; Singh, D.; Chatterjee, S.
Abstract: An organophosphorus pesticide malathion biodegradation was investigated by using the bacteria Ochrobactrum sp. M1D isolated from a soil sample of peach orchards in Palampur, District Kangra, Himachal Pradesh (India). The bacterium was able to utilize malathion as the sole source of carbon and energy. The isolated bacterium was found psychrotolerant and could degrade 100% of 100 mg l −1 malathion in minimal salt medium at 20°C, pH 7·0 within 12 days with no major significant metabolites left at the end of the study. Through GCMS analysis, methyl phosphate, diethyl maleate, and diethyl 2‐mercaptosuccinate were detected and identified as the major pathway metabolites. Based on the GCMS profile, three probable degradation pathways were interpreted. The present study is the first report of malathion biodegradation at both the psychrophilic and mesophilic conditions by any psychrotolerant strain and also through multiple degradation pathways. In the future, the strain can be explored to bio‐remediate the malathion contaminated soil in the cold climatic region and to utilize the enzymatic systems for advanced biotechnology applications. Abstract : Significance and Impact of the Study: Malathion is a neurotoxin pesticide extensively used worldwide for agricultural purposes which in turn causes many serious health hazards to the non‐targeted species. In the present study, a psychrotolerant bacterium was isolated and identified as Ochrobactrum sp. M1D, able to degrade 100 mg l −1 malathion efficiently within 12 days at 20°C, pH 7·0 through the three different degradation pathways. This is the first report of malathion degradation by any psychrotolerant Ochrobactrum sp. through multiple pathways. In the future, apart from the removal of malathion from contaminated soil in the cold climatic regions, one of the best utilization of this strain will be to explore the enzymatic system(s) for different biotechnology applications as the enzymes responsible for the degradation were found active at wide temperature ranges.